Notary Responsibility in Correcting Clerical and Typographical Errors in Deeds - Ni Kadek Arisya Citra Repinta; Ni Luh Made Mahendrawati; I Wayan Kartika Jaya Utama (Inovasi Pratama Internasional. Ltd, 2027)
This study constitutes normative legal research that analyzes the notary’s responsibility in correcting clerical and/or typographical errors in signed deeds, which plays an important role in ensuring the validity of deeds and legal certainty for the parties. The Notary Office Law grants notaries the authority to draw up authentic deeds concerning all legal acts, agreements, and stipulations required by statutory regulations. The focus of this study is the notary’s authority over clerical and/or typographical errors in the minuta deed, as well as the notary’s responsibility toward parties who suffer losses due to such errors in a minuta deed whose copy has already been issued. This research employs a conceptual approach and a statutory approach.Corrections are made in the presence of the appearers, witnesses, and notary, and are subsequently recorded in a deed of correction minutes. If an error causes losses to the parties, the notary may be held civilly, administratively, or criminally liable and is required to undertake corrective measures in accordance with the applicable legal provisions in order to ensure legal certainty, justice, and legal protection. The notary’s responsibility for typographical errors in a copied minuta deed is carried out through renvoi or by correcting the erroneous copy of the minuta deed, with initials affixed by the appearers, witnesses, and notary. Therefore, notaries must consistently uphold professionalism, accuracy, and the principle of prudence in carrying out their duties in order to ensure legal certainty and protect the interests of the parties